STUDENTS’ PERCEPTIONS TOWARD LEARNING MATERIALS USED IN ONLINE LEARNING - Nuryansyah Adijaya; Ratih Pertiwi (Universitas Ahmad Dahlan)
Online learning is assumed as a new paradigm in learning-teaching process in which lecturer and students do not need to sit in the same room to make class activities. They just need a gadget with internet connection to create the activities. Along with the practical of online learning, many institutions or universities in Indonesia create online learning to support learning-teaching process. However, online learning still faces some problems in learning activity, one of the problems is the use of learning materials. This study is aimed to explore students’ perceptions toward the use of learning materials in online learning whether the learning materials already support their activity in online class. 100 students of online learning TOEFL 2 are targeted to be research data. They are given some questions to explore their perceptions related to their perceptions toward the use of learning material. Besides, some students are also interviewed to explore deeper information. Quantitative analysis is employed in the study. This study reveals that students cannot decide whether learning material used in online learning already support online class or not which shown by mean score that reaches 2,805. they think materials are practical. However, they sometimes face some difficulties of using the materials; to understand instruction, responses, etc.These factors make students cannot decide their perception toward the use of learning material in online learning. That is why to support online learning, we must periodically revise learning materials for online learning.